Delimiting Channel Capacity: A Scrutiny of Challenges and New Developments - Jha, Amaresh; Vats, Aman (Journal of Advanced Research in Journalism & Mass Communication, 2017)
Objective: This study aims at identifying the capacity-related challenges of communication networks and makes an assessment of conceptual developments to address these challenges. Based on the review of such developments this paper enlists the knowledge gap and provides direction for further research. Method: This study uses meta-analyses method to combine and amalgamate the previous knowledge in the field of channel capacity optimization. Findings: Enhancing or optimizing the capacity of present day communication networks needs integration of approaches like providing additional bandwidth to the channel through free space optic technology, dynamic physical layering, algorithmic stacking of data and boosting the capability of network infrastructure. Limitations: Further elaboration on models of optical packet transmission and deep packet investigation for reducing the load from networks is needed. How to cite this article: Jha A, Vats A. Delimiting Channel Capacity: A Scrutiny of Challenges and New Developments. J Adv Res Jour Mass Comm 2017; 4(3&4): 14-19. DOI: https://doi.org/10.24321/2395.3810.201704